PENGEMBANGAN BUKU TEKS TENTANG PERADABAN MAKANAN POKOK BERBASIS PROJECT BASED LEARNING UNTUK MENUMBUHKAN KARAKTER RASA INGIN TAHU - Rastika Sagugubbaik, F.M.; Gregorius Ari Nugrahanta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Curiosity is an intrinsic drive that encourages individuals to acquire information and actively engage in the learning process. However, low levels of curiosity among students remain a persistent issue, characterized by limited initiative in asking questions and low participation in learning activities. This study aims to develop and examine the validity of a staple food civilization textbook based on Project Based Learning (PjBL) to foster students’ curiosity. The research employed a Research and Development (R&D) method using the ADDIE model and a quasi-experimental design. The research subjects consisted of ten certified teachers as needs analysis respondents, ten experts as feasibility evaluators, and fifth-grade students at a public elementary school in Yogyakarta, with class V A as the experimental group and class V B as the control group. The results showed that the developed textbook achieved a “very good” quality category with an average score of 3.81 on a 1–4 scale. The implementation of the textbook had a significant effect on students’ curiosity (p < 0.05) with an effect size of r = 0.81. The N-gain score of the experimental group was categorized as high (80.79), while that of the control group was categorized as low (14.70). Interrater reliability was classified as high (α = 0.756). Therefore, the developed Project Based Learning–based textbook is proven to be feasible, effective, and reliable as a learning medium and as a means to strengthen elementary students’ curiosity.